Descriptions of two new Pseudophacopteron species (Hemiptera: Psylloidea: Phacopteronidae) inducing galls on Aspidosperma (Apocynaceae) in Brazil - Malenovsky, Igor; Burckhardt, Daniel; Queiroz, Dalva L; Isaias, Rosy M S; Oliveira, Denis C (Acta entomologica Musei Nationalis Pragae, 2015)
Two new species of the large pantropical jumping plant-louse genus Pseudophacopteron Enderlein, 1921 (Hemiptera: Psylloidea: Phacopteronidae) are described from dry woodland habitats in the Midwest, Southeast and South of Brazil. Pseudophacopteron aspidospermi sp. nov. is associated with Aspidosperma australe, P. longicaudatum sp. nov. has been found on Aspidosperma macrocarpon and A. tomentosum (Apocynaceae). Both species induce intralaminar lenticular galls on the leaves of their host trees which have been the subject of several structural, histochemical and ecological publications. Adult males and females, fi fth instar immatures and galls are illustrated including diagnostic morphological details, and compared with other Neotropical and Old World species of Pseudophacopteron and Phacopteronidae. The distribution of Pseudophacopteron in the Neotropical Region is briefly discussed.